A hydrophilic coumarin-based polyester for ambient-temperature initiator-free 3D printing: Chemistry, rheology and interface formation. (12th September 2018) - Govindarajan, Sudhanva R.; Jain, Tanmay; Choi, Jae-Won; Joy, Abraham; Isayeva, Irada; Vorvolakos, Katherine
Abstract: Initiator-free, photocurable, low-toxicity, viscoelastic polymer inks are attractive materials for creating low-modulus 3D-printed elastomeric biomedical constructs. In this work, we describe the synthesis, characterization, and 3D printing/crosslinking of a hydrophilic coumarin-PEG polyester ( CPP ). The viscoelastic CPP melt can be extruded at room temperature and deposited into layer-by-layer patterns. Upon UV irradiation, the coumarin pendant groups undergo [2 + 2] photocyclization, creating a thermoset network without the use of monomers, photoinitiators or propagating radicals. Voxel-voxel adhesion experiments between crosslinked and uncrosslinked material were performed to examine interfacial dynamics in a native, unperturbed state, and various attempts at 3D printing were made to assess the impact of printing conditions on the ultimate printed structure. Rheological analysis indicates a transition point where elastic behavior overtakes viscous behavior at increasing shear rate. It is hypothesized that this transition point corresponds with changes in interface formation from "sticky" to "bouncy" behavior in voxel-voxel adhesion and 3D printing processes. Tensile-mode dynamic mechanical analysis (DMA) and X-Ray microtomography (microCT) experiments reveal interfacial defect accumulation that results in deterioration of macroscopic structural and mechanical properties. Graphical abstract: Highlights: Coumarin, which is UV-photoreactive, has been incorporated into a polymer backbone. It allows for tunable network crosslinking without additional chemical components. The crosslinked polymer, a coumarin-PEG polyester (CPP ), swells with water. CPP can be 3D-printed in its dry melt state and turned into a degradable hydrogel.